Improving Antimicrobial Activity and Physico-Chemical Properties by Isosteric Replacement of 2-Aminothiazole with 2-Aminooxazole - Juhás, Martin; Bachtíková, Andrea; Nawrot, Daria Elżbieta; Hatoková, Paulína; Pallabothula, Vinod Sukanth Kumar; Diepoltová, Adéla; Janďourek, Ondřej; Bárta, Pavel; Konečná, Klára; Paterová, Pavla; Šesták, Vít; Zitko, Jan (Pharmaceuticals, 2022)
Antimicrobial drug resistance is currently one of the most critical health issues. Pathogens resistant to last-resort antibiotics are increasing, and very few effective antibacterial agents have been introduced in recent years. The promising drug candidates are often discontinued in the primary stages of the drug discovery pipeline due to their unspecific reactivity (PAINS), toxicity, insufficient stability, or low water solubility. In this work, we investigated a series of substituted N-oxazolyl- and N-thiazolylcarboxamides of various pyridinecarboxylic acids. Final compounds were tested against several microbial species. In general, oxazole-containing compounds showed high activity against mycobacteria, especially Mycobacterium tuberculosis (best MICH37Ra = 3.13 μg/mL), including the multidrug-resistant strains. Promising activities against various bacterial and fungal strains were also observed. None of the compounds was significantly cytotoxic against the HepG2 cell line. Experimental measurement of lipophilicity parameter log k'w and water solubility (log S) confirmed significantly (typically two orders in logarithmic scale) increased hydrophilicity/water solubility of oxazole derivatives in comparison with their thiazole isosteres. Mycobacterial β-ketoacyl-acyl carrier protein synthase III (FabH) was suggested as a probable target by molecular docking and molecular dynamics simulations.